The TRT Female Remeex System® for recurrent female stress urinary incontinence: A 5-year follow-up study. (May 2013) - Barrington, J.; Archer, R.; Kulkarni, M.; Forrest, A.
<x xml:space="preserve">Abstract</x> Conventional surgery for female stress incontinence is usually successful but recurrent cases are difficult to treat. This study of 20 such cases treated by the Remeex TRT system shows symptomatic benefit up to 5 years following insertion of the device. The benefit of this procedure is that the sling can be adjusted to the correct tension in the optimum leak position and circumstances, and anytime thereafter without the need to repeat the entire operation. As a result, the voiding dysfunction rate and need to intermittent self-catheterise is reduced, even with a low pressure urethra. The cost per procedure and complication rate is higher that standard TVT, and the device may occasionally need removal due to persistent seroma. However, the improved quality of life makes this operation an attractive option in recurrent cases of female stress incontinence.